Implementasi English for Specific Purposes (ESP) dalam Pembelajaran Bahasa Inggris pada Program Studi Pendidikan Bahasa Inggris Universitas Ekasakti Padang - Elda Marta Suri; Dewi Kristiani Bawamenewi (LPPM Universitas Ekasakti, 2025)
The implementation of English for Specific Purposes (ESP) in English language education is increasingly relevant in the context of globalization, particularly in higher education aimed at preparing students for professional demands. This study aims to analyze the implementation of ESP instruction in the English Education Study Program, Faculty of Teacher Training and Education, Universitas Ekasakti Padang. A qualitative descriptive method was employed, involving classroom observation, interviews with lecturers and students, and analysis of syllabi and teaching materials. Findings indicate that ESP is partially applied, focusing on the development of academic and vocational language competencies. However, several challenges persist, such as limited lecturer training in ESP pedagogy and the lack of domain-specific teaching resources. The study concludes that successful ESP implementation requires institutional support, ongoing professional development, and curriculum adaptation based on needs analysis.